Substations power quality improvement by flexible alternating current transmission system devices - Faissl G Chremk Chremk; Hanene Medhaffar (Institute of Advanced Engineering and Science, 2024)
The increase in load demand has a negative impact on power system quality, reliability, and stability. Transporting reactive power from the generating side to the distribution side reduces the transmission line’s capacity to deliver active power to loads. In conventional power systems, during faults or sudden loads, the load flow changes and causes extra voltage drop. Reactive power compensation at the load side can improve voltage quality at distribution busbars, but the conventional compensation method doesn’t offer the required flexibility. With the development of the power electronics industry, flexible alternating current transmission system (FACTS) devices have been introduced. There are many categories for FACTS controllers, including series, shunt, and hybrid, which can exhibit dynamic operating characteristics. In this paper, two types of FACTS devices (STATCOM and fixed capacitor-thyristor-controlled reactors (FCTCR)) have been used to improve voltage profile in a part of Iraq’s high voltage power system during unusual operating conditions, such as sudden loads and the absence generation. Load flow calculations were conducted to determine the critical bus, and then the performance of the FACTS devices was investigated during heavy loading when the devices were connected separately to the critical bus. The voltage drop in the bus was 1.58%, which reduced to 0.78% with STATCOM and 0.96% with FCTCR.